Implementation of Educational Technology and Teacher Support through Service Learning in Early Childhood Education to Enhance Basic Skills - Marlina, Yuli; Irsyadiah, , Nur; Oktoriano S, Adriano; Soraiya (STAI Miftahul ULa Nganjuk, 2025)
This community service project focuses on the integration of educational technology in early childhood education, particularly at Pre-School Little Bear Indonesia, to enhance children's basic skills. The primary issue addressed is the readiness of educators in utilizing technology, along with the challenges in providing digital-based learning resources and strategies. The goal of this service project is to build teachers' capacity in using technology effectively, develop a technology-based curriculum, and evaluate the impact of technology on children's critical thinking, creativity, and social interaction skills. The approach used is Service Learning (SL), which involves teacher training, classroom observations, interviews with parents, and evaluative surveys on the use of digital media. The results show that educational technology can increase children's engagement in learning, but it requires infrastructure support and continuous teacher training to ensure its optimal and sustainable implementation.